Statin‐induced autoimmune necrotizing myositis—A single‐center case series highlighting this potentially life‐threatening but treatable condition. Issue 12 (27th October 2020) - Jasim, Muhamad; Sapkota, Hem; Timmons, Margaret; Manfredonia, Francesco; Pohl, Ute; Barkham, Nick
Abstract: Statin‐induced autoimmune necrotizing myositis is a rare but important cause muscle weakness. Withdrawal of the statin and steroid treatment alone may be insufficient treatment for SIANM. Targeted immunosuppression may be needed and can be effective. Abstract : Statin‐induced autoimmune necrotizing myositis is a rare but important cause muscle weakness. Withdrawal of the statin and steroid treatment alone may be insufficient treatment for SIANM. Targeted immunosuppression may be needed and can be effective.